Electrochemically enabled (3+2) cycloaddition of unbiased alkenes and β-dicarbonyls - Suryawanshi, Sharad M.; Sahoo, Suman; Shaligram, Parth S.; Manna, Narugopal; Samanta, Ramesh C. (Chemical Communications, 2024)
A (3+2) cycloaddition between unbiased alkenes and 1,3-dicarbonyls is accomplished by judicious choice of electrode material and electrocatalyst to access dihydrofuran derivatives. A fluorinated porous carbon electrode with appropriate thickness governs unprecedented reactivity. This methodology eliminates the necessity for any stabilizing group within the alkene substrate. This is a rare example of the annulation of unbiased internal and terminal alkenes with cyclic and acyclic beta-dicarbonyls.
Keywords: 1; 3-DICARBONYL COMPOUNDS; DIHYDROFURANS; FACILE SYNTHESIS

Electrochemical generation of N-centered radicals and their reactivity toward cyclization and subsequent C―C bond cleavage - Suryawanshi, Sharad M.; Singh, Mayuri; Samanta, Ramesh C. (Helvetica Chimica Acta, 2026)
N-containing heterocycles are widely used in medicinal chemistry, and they can be synthesized efficiently by the intramolecular cyclization of N-centered radicals. Furthermore, N-centered radicals also act as excellent hydrogen atom transfer (HAT) reagents. On the other hand, nitrogen atoms in the nitrogen-containing heterocycles are used as a handle to cleave stable five and six-membered rings. However, the electrochemical generation of N-centered radicals and their application in forming heterocycles have been extensively studied. Study beyond cyclization remains largely unexplored; in this manuscript, we summarize our new findings as follows. Under electrochemical conditions, the N & horbar;H bond is cleaved, forming an N-centered radical that adds to the double bond in a 6-endo-trig cyclization fashion. The newly formed C-centered radical reacts with oxygen and undergoes C & horbar;C bond cleavage to form the corresponding carbonyl compounds. The reactivity is dependent on the substituents present on nitrogen. In the case of aromatic amine-derived amide, the TEMPO trapping cyclization product was isolated. A mechanism has been proposed to explain the formation of the products.
Keywords: C-C bond cleavage; cyclization; N-centered radical; N-heterocycles; oxidative ring opening